The world of castles and forts - Day, Malcolm (1996)
An illustrated history of castles and forts through the ages, from Mycenaean citadels to bomb shelters.
Originally published: Keep out! Hemel, Hempstead, Herts : Macdonald Young Books Ltd., c1995.
Includes index.
Keywords: Fortification -- Juvenile literature; Castles -- Juvenile literature